S100A7 overexpression is a predictive marker for high risk of malignant transformation in oral dysplasia. Issue 6 (8th October 2013) - Kaur, Jatinder; Matta, Ajay; Kak, Ipshita; Srivastava, Gunjan; Assi, Jasmeet; Leong, Iona; Witterick, Ian; Colgan, Terence J.; MacMillan, Christina; Siu, K.W. Michael; Walfish, Paul G.; Ralhan, Ranju
<x xml:space="preserve">Abstract</x> Early detection of oral lesions (OLs) at high risk of cancer development is of utmost importance for intervention. There is an urgent unmet clinical need for biomarkers that allow identification of high‐risk OLs. Recently, we identified and verified a panel of five candidate protein biomarkers namely S100A7, prothymosin alpha, 14‐3‐3ζ, 14‐3‐3σ and heterogeneous nuclear ribonucleoprotein K using proteomics to distinguish OLs with dysplasia and oral cancers from normal oral tissues. The objective of our study was to evaluate the potential of these candidate protein biomarkers for identification of oral dysplastic lesions at high risk of cancer development. Using immunohistochemistry, we analyzed expressions of these five candidate protein biomarkers in 110 patients with biopsy‐proven oral dysplasia and known clinical outcome and determined their correlations with p16 expression and HPV 16/18 status. Kaplan–Meier survival analysis showed reduced oral cancer‐free survival (OCFS) of 68.6 months (p = 0.007) in patients showing cytoplasmic S100A7 overexpression when compared to patients with weak or no S100A7 immunostaining in cytoplasm (mean OCFS = 122.8 months). Multivariate Cox regression analysis revealed cytoplasmic S100A7 overexpression as the most significant candidate marker associated with cancer development in dysplastic lesions (p = 0.041, hazard ratio = 2.36). In conclusion, our study suggested the potential of S100A7 overexpression in identifying OLs with dysplasia at high risk of cancer development.